Morphological characterization of maize genotypes in Sylhet - Islam, Md Tazul; Swapna, Sabiha Akter; Islam, AFM Saiful; Uddin, Saraf; Raihan, Md Sazzat Hossain; Mallick, Sharmita Rani; Baki, Md Abdul (Research in Agriculture Livestock and Fisheries, 2023)
Maize plays an important role both as food and feed throughout the world. For morphological characterization and evaluation of yield attributes of maize genotypes an experiment was carried out at the experimental field of the Department of Crop Botany and Tea Production Technology, Sylhet Agricultural University (SAU). The experimental materials were seven exotic maize genotypes viz.ZM 0001, ZM 0002, ZM 0003, ZM 0004, ZM 0005, ZM 0006ZM 0007 along with BARI Maize 6 as control. The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications. Significant variations were observed among eight maize genotypes for most of the plant characters studied. The tallest plant was found in ZM 0005(246.5 cm). The highest number of leaves was produced in ZM 0001 (14.01). The longest and widest leaf was recorded in ZM 0004 (94.67 cm) and BARI Maize 6 (10.32 cm), respectively. The longest internode was found in ZM 0004 and ZM 0005 (21.61 cm). The genotype ZM 0004 was the earliest in respect of tasseling and silking. Ear height was highest in ZM 0005 (143.8 cm). The genotype ZM 0004 matured the earliest (109.3 days) while BARI Maize 6 matured the last (126 days). No variation was found for ear shape but in terms of kernel color, kernel type, kernel row arrangement and shape of upper surface of the kernel there were great variations among the genotypes. BARI Maize 6 produced the largest kernel with the highest thousand kernel weight. Grain yield plant-1 t ha-1 was highest in BARI Maize 6 which was closely followed by ZM 0005 and ZM 0004 among the studied genotypes. A correlation study between the yield and yield contributing characters showed that ear length, ear diameter, number of kernels row-1, kernel length, kernel width, kernel thickness, thousand kernel weights, and the weight of kernels ear-1, prolificacy index and weight of kernels plant-1 had a significant positive correlation with grain yield. Vol. 10, No. 1, April 2023: 21-32